Features of temperature-dependent internal friction at phase decomposition of Nb-Ti alloy - Arzhavitin, V.M. (Functional Materials, 2008)
Experimental dependence of internal friction Q⁻¹(T) on heating temperature T of pre-strained Nb-(48.5±1,5)Ti (wt. %) alloy is a superposition of two internal friction peaks with maxima at 250°C and 300°C. It is shown by calculation that both the peaks are due to nucleation and subsequent diffusion-controlled growth of a-Ti segregates in the walls of dislocation cells. The first peak is connected with Ti diffusion in the cell boundaries while the second one, in the volumes thereof.